Cross-cultural adaptation, reliability, and validity of the vestibular rehabilitation benefit questionnaire in the central Kurdish version - Bafrin Ghafoor Majeed; Sherko Saeed Fatihullah Zmnako; Hiwa Asaad Abdulkareem (Advanced Medical Journal)
Background and objectives: The vestibular rehabilitation benefit questionnaire is a new patient-reported outcome measures with psychometric properties, to assess the efficacy of vestibular rehabilitation. The present study aims to cross-culturally adapt the questionnaire into the central Kurdish dialect and to examine its psychometric properties.